Pengaruh Media Tanam dan SADH terhadap Pertumbuhan dan Perkembangan Tanaman African Violet (Saintpaulia ionantha) - Fitria Sari; Nurhajati Ansori Mattjik (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2004)
The purpose of the experiment was to identify the effect of growing medium and SADH (Succunic Acid Dimethyl Hydrazide) on growth and development of African Violet (Saintoaulia ionanthqJ. The experiment was conducted in Baranang Siang Bogor (240 m above sea level), and arranged in factorial randomized complete block design. The first factor was medium (1 cocopeat : 1 sand : 1 compost ; 1 cocopeat : 2 sand : 1 compost ; 1 cocopeat : 1 sand : 2 compost ; 2 cocopeat : 1 sand : 1 compost). The second factor was concentration of SADH (0, 15, 30, 45 mg/l). There was not significant effect of medium and SADH qn vegetative growth, except leaf area. SADH (15 mg/l) and medium 4 (2 cocopeat : 1 sand : 1 compost) had largest leaf Growing medium and SADH had significant effect on generative growth especially on time to visible flower buds, flower bud number, flower number, flower diameter and flower senessence. SADH (15 mg/l) applied to medium 4 (2 cocopeat : 1 sand : 1 compost) initiated time to flower. SADH (30 mg/l) applied to medium 4 affected to highest number of flower buds, and SADH (0 mg/l) applied to growing medium 4 affected highest flower diameter.